Associativismo e desenho institucional no Orçamento Participativo da região metropolitana do Espírito Santo - Euzeneia Carlos (Ciências Sociais Unisinos)
This article presents a study about the participatory budgeting in three municipalities of the metropolitan region of Espírito Santo, viz. Vitória, Serra and Carapina. It examines the representatives' political behavior in the participatory budgeting in two dimensions: the actors' associativism and their perception of authority and influence in the decision making process. The study affirms the relevance of the variables, associativism and institutional design for the understanding of participation in the institutionalized arrangements. The analysis demonstrates that associativism encourages the actors' participation in the institutionalized channels, whereas the perception of authority by the social representatives correlates with the institutional design of the participatory arrangements.